An Analysis of Deixis in “Die With A Smile” By Bruno Mars And Lady Gaga - Risma Silviana Rindi; Syifa’ Khuriyatuz Zahro (Insan Akademika Publications, 2025)
Language shows a significant part in social interaction, not only as a means of communication but likewise as a medium to express identity, emotion, and perspective. One of the pragmatic features that reveals how language relates to context is deixis. This research purposes to examine the categories and functions of deixis in the lyrics of “Die With a Smile”, a collaborative song by Bruno Mars and Lady Gaga. Using a descriptive qualitative method, the research focused on identifying and categorizing deictic expressions based on Levinson’s (1983) and Yule’s (1996) typology: person, spatial, and temporal deixis. The data were collected through documentation and examined through content examination to interpret the contextual implication of each deictic term. The findings revealed a total of 30 deictic expressions in the lyrics, dominated by personal deixis with 22 occurrences (73.33%), mainly through the pronoun “I.” Temporal deixis, such as “tomorrow” and “last night,” added emotional depth, while spatial deixis like “the world” and “wherever” conveyed abstract or symbolic locations. These deixes not only clarified the speaker’s intentions but also strengthened the emotive linking between the vocalist and listener. The study contributes to pragmatic linguistic analysis in music by highlighting how deixis shapes meaning and perspective. However, the study is inadequate to a single song and three types of deixis. Future studies are encouraged to analyze other songs, genres, or types of deixis, as well as explore multimodal elements such as music video visuals to increase a more inclusive thoughtful of meaning construction in popular music